Pengukuran Kinerja Bank Perkreditan Rakyat di Indonesia dengan Pendekatan Quantitative Aspect - Supriyanto Supriyanto; Sisca Mediyanti; Ramadhan Razali; Rita Nengsih; Wardayani Wardayani (PERSPEKTIF, 2020)
This study is aimed to measure Rural Bank performance through a Quantitative Aspect approach based on the RGEC Methods. The financial ratios used are Loan to Deposit Ratio, Non-Performing Loans, and Return on Assets, The objects of the research are the Conventional Rural Banks in Indonesia with totally 1,545 companies, where whole population being the study sample. The data calculated were conveyed from the Indonesian Banking Statistics Period 2015 - 2019, through the Financial Services Authority website, then being analyzed by using Descriptive Statistics method. Descriptive statistical method is a way of collecting and presenting data in the form of data centralization so that the data provide useful information. The results of the study shows that the Performance of Rural Credit Banks in Indonesia in the 2015 - 2018 period based on the quantitative aspect approach was generally stated as good category. By considering the height of NPL, it is indicated that Rural Bank Management is more prudent in providing financing which is marked by good category LDR value.. The positive impact of the management's prudent way is the high level of Rural Banks profitability that is measured by the ROA value in good category.